Conserving coffee genetic resources: Complementary strategies for ex situ conservation of coffee (Coffea arabica L.) genetic resources. A case study in CATIE, Costa Rica - Engelmann, F.; Dulloo, Mohammad Ehsan; Astorga, C.; Dussert, S.; Anthony, F. (2007)
It is now well recognized that an appropriate conservation strategy for plant species requires a holistic approach which combines ex situ and in situ conservation techniques in a complementary manner. Selection of appropriate methods should be based on a range of criteria, such as biological nature of the species, practicality and feasibility of the method, as well as the cost-effectiveness and security. Complementary conservation strategies are of particular relevance for species with seeds displaying non-orthodox storage behaviour, such as coffee, traditionally stored in field genebanks. This publication describes the application of cryopreservation techniques tested in the CATIE genebank which holds one of the largest field collections of coffee worldwide, mainly Coffea arabica, in the framework of an ex situ complementary conservation strategy. It aims to stimulate research on complementary conservation strategies for other problem crops, as well as on the biotechnological tools required to implement them.